8.- THE DISCIPLINARY CULTURE OF CITATION IN SCIENTIFIC ARTICLES IN THE HUMANITIES - Komesu, Fabiana; Alves Assis, Juliana; Donahue, Christiane (Nueva Revista del Pacífico, 2023)
Abstract: This article aims to identify and analyze aspects that are not dealt with or cannot be visualized in the bibliometric indexes of journals and articles in the Humanities, specifically in the field of Linguistics. This study is based on a data set of the “citing texts” (114) of three articles of the field of Linguistics that come from a Brazilian journal, a Chilean journal and a South African journal, among the most cited articles of the journals Scielo basis (Google Scholar data) in the month of September, 2021. The methodological procedures take into account the criteria (i) year of publication of the citing texts, (ii) language of publication of the citing texts, (iii) discourse genre of the citing texts, and (iv) location of the institution to which the author(s) of the citing texts are affiliated. The results problematize a culture restricted to bibliometric indexes. Resumen: Este artículo tiene como objetivo identificar y analizar aspectos que no son tratados o no pueden ser visualizados en los índices bibliométricos de revistas y artículos de Humanidades, específicamente en el campo de la Lingüística. Este estudio se basa en un conjunto de datos de los “textos a citar” (114) de tres artículos del campo de la Lingüística que provienen de una revista brasileña, una revista chilena y una revista sudafricana, entre los artículos más citados de las revistas base Scielo (datos de Google Scholar) en el mes de septiembre de 2021. Los procedimientos metodológicos tienen en cuenta los criterios (i)año de publicación de los textos citados, (ii) lengua de publicación de los textos citados, (iii) género del discurso de los textos citados y (iv) localización de la institución a la que pertenecen el autor o los autores de los textos citados. Los resultados cuestionan una cultura restringida a los índices bibliométricos.